Enhanced Photocatalytic Oxygen Evolution by Crystal Cutting. (20th January 2013) - Sun, Min; Xiong, Shijie; Wu, Xinglong; He, Chengyu; Li, Tinghui; Chu, Paul K.
<x xml:space="preserve">Abstract</x> Uniformly cut In2O3 truncated octahedrons are fabricated on a large scale by a simple chemical vapor deposition (CVD) technique. This theoretical analysis predicts that the emergence of 100 facets on the In2O3 truncated octahedrons enhances oxygen evolution significantly in photocatalysis and experimental photoelectrochemical measurements are consistent. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>